Primeiro estudo do uso de termografia escrotal em touros girolando e sua relação com a classificação andrológica por pontos - Moreira, Gabriel Miranda (2016)
Breeding soundness evaluation (BSE) is a method that allows the selection of bulls with greater reproductive potential. The performance of bulls evaluated by BSE system may be influenced by the scrotum surface temperature, which is related to the environmental temperature. The objective was to verify the relationship to the scrotal surface thermographic temperatures and the BSE in Girolando bulls. Scrotal circumference (SC), testicular volume (TESTVOL), spermatic chord length (SCL), scrotum skin texture (SST), motility, vigor, mass motion, major defects (MAD), minor defects (MID), and total defects (TOD) were evaluated in sixty eight Girolando bulls. Three classes were established according to the BSE score: unsatisfactory (0-29), questionable (30-59) and satisfactory (60-100). The scrotal surface and the ocular region thermographic temperatures were evaluated. A temperature and humidity index (THI) was calculated when photographs were taken. The SC and TESTVOL of satisfactory and questionable bulls were greater (P<0.01). Age, weight, SCL, SST, seminal physical parameters, MID and scrotum surface thermographic temperatures were similar (P>0.05) between BSE classes. The THI was positively correlated (P<0.01) to the scrotum and ocular region thermographic temperatures. The thermographic temperatures of the scrotum surface were not limiting to the BSE performance of bulls.